ENVIRONMENTAL STANDARDS IN URBAN PLANNING AND THEIR APPLICATION - Normatov Ermamat Toyir o‘g‘li (International Journal of Business, Law and Political Science, 2026)
Objective: This article examines the legal foundations of environmental standards in the field of urban planning in Uzbekistan, the challenges in their practical implementation, and ways to improve them. It analyzes pressing environmental issues such as the acceleration of urbanization, air pollution, the reduction of green areas, and illegal construction. Method: Environmental requirements are reviewed based on the Urban Planning Code and relevant regulatory documents. A comparative analysis is conducted with international experience, including European Union directives and the “smart city” models of Singapore and Dubai. Results: The proposed recommendations focus on digitalizing monitoring systems, developing the “green city” concept, and strengthening regulatory oversight. Novelty: The study contributes to sustainable urbanization and the transition to a green economy.